Expression Profiles of the Heat Shock Protein 70 Gene in Response to Heat Stress in Agrotis c-nigrum (Lepidoptera: Noctuidae). Issue 1 (16th February 2015) - Wang, Ling; Yang, Shuai; Zhao, Kuijun; Han, Lanlan
Abstract : Heat shock proteins (HSPs) are molecular chaperones, and their overexpression enhances the survivability and stress tolerance of the cell. To understand the characteristics of HSP70 in Agrotis c-nigrum Linnaeus larvae, the coding sequence of this protein was cloned, and the effect of heat stress on transcription and protein properties was assessed. The obtained cDNA sequence of HSP70 was 2, 213 bp, which contained an ORF of 1, 965 bp and encoded 654 amino acid residues. Isolated HSP70 cDNA demonstrated more than 80% identity with the sequences of other known insect HSP70s. Next, HSP70 was expressed in Escherichia coli BL21 (DE3) cells and identified using SDS-PAGE and western blotting analyses. In addition, anti-HSP70-specific antisera were prepared using a recombinant HSP70 protein, and the results showed that this antisera was very specific to Ac HSP70. Real-time quantitative polymerase chain reaction detected the relative transcription of the HSP70 gene in larvae and the transcription of A. c-nigrum in response to high temperatures. Induction of HSP70 was up-regulated to peak expression at 36°C.